NH3+N2O3 reaction. High level calculations - Morgon, N. H.; Souza, Aguinaldo Robinson de [UNESP]; Sambrano, JR (Elsevier B.V., 2006)
We have undertaken a comprehensive study of the NH3 + N2O3 reaction in gas phase. Total energies of reactants, intermediates, transition states, and products have been calculated at CBS-QB3 level of theory. The corresponding BSSE analysis were performed at the highest level of theory, i.e. MP2 using the complete basis set (CBS) extrapolation at CBS-QB3 optimized geometries. A detailed mechanism was proposed for 2NH(3) - N2O3 -> 2N(2) - 3H(2)O with Delta H-r= - 170.08 kcal/mol N-2. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: reaction of nitrosation; CBS-QB3 calculations; N2O3